Development and characterization of spray dried batuan (Garcinia binucao (Blanco) Choisy) powder. - Cornelio, April Rose C.
Batuan is considered as a seasonal and a highly perishable fruit. It is also known as a souring agent for different soup dishes in the Philippines and in other countries. There have been a lot of attempts in transforming the fruit into a conventional processed form with increased shelf-life to make the advantages of the fruit year round. Improving the availability of the fruit and its use led to the development of batuan powder. Developing a powdered form of this commodity was done by spray drying. Three formulations for the batuan form of this commodity was done by spray drying. Three formulations for the batuan powder used as a souring agent in soup were made. The formulations were 10% (F1), 15% (F2) and 20% (F3) (w/v basis). The analyses of the powder were pH,TSS, TA, aw, miosture, protein, ash, fat, and fiber determination and sensory analysis. Prior to analyzing the most preferred formulation, the physicochemical composition and moisture content of the fresh batuan was also determined. Batuan powder contains low amount of fat (0.13%), protein (0.24%), fiber (1.18%), and ash (0.35%). Furthermore, it contains high amount of carbohydrate (96.80%) due to the addition of maltodextrin. The physicochemical composition, namely, pH (2.11), TA (0.23%), and aw (0.31) of batuan powder was lower compared to the fresh fruit. The TSS (92.14%) of the powder was higher compared to the fresh fruit because maltodextrin was added. Among the three formulations, Formulation 3 (20%) was chosen to be the most preferred formulation. It also had the highest intensity of sourness among the three formulations. It was also chosen by the panelists to have greater intensity of the sourness compared to the fresh batuan fruit. The process of encapsulating the flavor of the fruit using maltodextrin resulted for the flavor to linger more in the palate. The general acceptability of the most preferred formulation used as a souring agent in a soup was 8 (like very much) with rating of 46%. Generally, the batuan powder was acceptable to be used as an alternative souring agent in soup dishes.